PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA AUDIOVISUAL TESTIMONI ODHA DALAM MENURUNKAN STIGMA TERHADAP ODHA PADA MAHASISWA TINGKAT I AKPER PANTI KOSALA SURAKARTA - Wiwin Winarni; Briantoko Lilih Waluyo Utomo (KOSALA : Jurnal Ilmu Kesehatan, 2019)
Giving stigma toward people who live with HIV/AIDS is not only can be found on common people lives in society but also among health workers. It is unbelievable if health workers whose education background is health will do the same thing toward people living with HIV/AIDS. Thus, it is necessary to have some strategies to prepare nursing students in order to reduce the discrimination which happen in health services facilities by health workers. Hence, the prevention efforts of HIV/AIDS cases in Indonesia can optimally be implemented. The purpose of this study was to analyze the effect of health education through testimonial method in reducing stigma toward people living with HIV/AIDS on first year students in Panti Kosala Surakarta Nursing Academy. This research used quasy experiment with pre post experimental design. The total population involved in this research were 106 first year students of Panti Kosala Nursing Academy. Total sampling was used as a sampling technique. Data was collected by using questionnaire. The data was then analyzed using Wilcoxon aided by SPSS serial 18. There were three main results of this study : 1) The vast majority of first year students has high level of education about HIV/AIDS (98.11%) and low level of stigma toward people living with HIV/AIDS (55.66%) before had been given intervention. 2) The majority of first year students has high level of education about HIV/AIDS (99.05%) and low level of stigma toward people living with HIV/AIDS (95.28%) after had been given intervention. 3)The analysis Wilcoxon shows significancy number p<0,000. It can be concluded that health education through testimonial video has given significant effect in reducing stigma toward people living with HIV/AIDS on first year students in Panti Kosala Surakarta Nursing Academy. Keywords: health education, audiovisual, stigma, people living with HIV/AIDS